Gene expression patterns in synchronized islet populations. Issue 2 (4th March 2019) - Mukhitov, Nikita; Adablah, Joel E.; Roper, Michael G.
ABSTRACT: In vivo levels of insulin are oscillatory with a period of 5–10 minutes, indicating that the islets of Langerhans within the pancreas are synchronized. While the synchronizing factors are still under investigation, one result of this behavior is expected to be coordinated and oscillatory intracellular factors, such as intracellular Ca 2+ levels, throughout the islet population. In other cell types, oscillatory intracellular signals, like intracellular Ca 2+, have been shown to affect specific gene expression. To test how the gene expression landscape may differ between a synchronized islet population with its reproducible intracellular oscillations and an unsynchronized islet population with heterogeneous oscillations, gene set enrichment analysis (GSEA) was used to compare an islet population that had been synchronized using a glucose wave with a 5-min period, and an unsynchronized islet population. In the population exposed to the glucose wave, 58/62 islets showed synchronization as evidenced by coordinated intracellular Ca 2+ oscillations with an average oscillation period of 5.1 min, while in the unsynchronized population 29/62 islets showed slow oscillations with an average period of 5.2 min. The synchronized islets also had a significantly smaller drift of their oscillation period during the experiment as compared to the unsynchronized population. GSEA indicated that the synchronized population had reduced expression of gene sets related to protein translation, protein turnover, energy expenditure, and insulin synthesis, while those that were related to maintenance of cell morphology were increased.